2019
DOI: 10.2351/1.5096079
|View full text |Cite
|
Sign up to set email alerts
|

Toward application of hierarchical structures by ultrashort pulsed laser ablation

Abstract: Surface structuring is a versatile tool to modify the physical interplay at the interface to gaseous or liquid media. The two industrial used approaches are, in general, a chemical modification via coating or/and an introduced topography. Here, the structuring is carried out with a direct technique using an ultrashort pulsed laser with infrared and green wavelengths. Two hierarchical structural units are generated at the surface on copper, aluminum, and an amorphous alloy. Structures in the micrometer regime a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Considering the uniqueness of LSFLs/UHSFLs obtained by fs-LA, it is highly desirable to integrate them onto microstructures in order to construct multiscale hierarchical micro/nanostructures, which will promise the generation of specific functions. To date, although many hierarchical micro/nanostructures [34,35] have been created and some of them have been applied in cellular behavior control [36,37], color imprinting [38], antireflectance [35,39,40] and superhydrophobicity/superoleophobicity [41][42][43], a report on the preparation and application of LSFLs/UHSFLs-containing hierarchical micro/nanostructures is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the uniqueness of LSFLs/UHSFLs obtained by fs-LA, it is highly desirable to integrate them onto microstructures in order to construct multiscale hierarchical micro/nanostructures, which will promise the generation of specific functions. To date, although many hierarchical micro/nanostructures [34,35] have been created and some of them have been applied in cellular behavior control [36,37], color imprinting [38], antireflectance [35,39,40] and superhydrophobicity/superoleophobicity [41][42][43], a report on the preparation and application of LSFLs/UHSFLs-containing hierarchical micro/nanostructures is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to limiting constraints, where high average power must be distributed on the workpiece by high scan speeds and repetition rates [21]. To date there is plenty of laser power with high repetition rates available, but depending on the necessary focal spot size the beam steering [22] or controllers [23] are constraining the maximal laser machining speed. Using the laser in a burst mode with small temporal pulse spacing can enhance the maximal applicable average power [24] and ablation rate [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For the achievement of this kind of surface properties, the use of pulsed laser irradiation techniques has proven to be a clearly effective procedure, different conceptual approaches having been the subject of research and extensively reported in the literature [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%